Pubertal testosterone correlates with adolescent impatience and dorsal striatal activity. (April 2020) - Laube, Corinna; Lorenz, Robert; van den Bos, Wouter
Highlights: Results show that pubertal testosterone modulates dorsal, not ventral, striatal function in an intertemporal choice task. In addition, increased levels of testosterone are associated with a greater response bias towards choosing the smaller sooner reward. Findings suggest that pubertal testosterone may modulate local control processes, particularly in the dorsal striatum. Abstract: Recent self-report and behavioral studies have demonstrated that pubertal testosterone is related to an increase in risky and impulsive behavior. Yet, the mechanisms underlying such a relationship are poorly understood. Findings from both human and rodent studies point towards distinct striatal pathways including the ventral and dorsal striatum as key target regions for pubertal hormones. In this study we investigated task-related impatience of boys between 10 and 15 years of age ( N = 75), using an intertemporal choice task combined with measures of functional magnetic resonance imaging and hormonal assessment. Increased levels of testosterone were associated with a greater response bias towards choosing the smaller sooner option. Furthermore, our results show that testosterone specifically modulates the dorsal, not ventral, striatal pathway. These results provide novel insights into our understanding of adolescent impulsive and risky behaviors and how pubertal hormones are related to neural processes.